Solitary - Smith, Alexander Gordon, 1979- (New York : Farrar Straus Giroux, 2010)
Imprisoned for a murder he did not commit, fourteen-year- old Alex Sawyer thinks that he has escaped the hellish Furnace Penitentiary, but instead he winds up in solitary confinement, where new horrors await him.
Accelerated Reader AR
Keywords: Prisons -- Juvenile fiction; Horror tales; Science fiction